Lesson - Learned of Success in Chinese Teaching – Learning of Confucius classroom, Phuket Wittayalai School - แก้วบุตร, พิชัย (Trends of Humanities and Social Sciences Research, 2020)
The objectives of this research is to study and analyze all factors in various aspects which resulted effectively to the teaching - learning management of the Confucius Classroom at Phuket Wittayalai school and is accepted widely. The research found that the factors which effect the Chinese teaching - learning at Confucius Classroom, Phuket Wittayalai School is effectively and widely accepted are divided into 3 factors as follows; 1) Internal factors, Confucius Classroom, Phuket Wittayalai School has arranged the obvious and intensive Chinese curriculum, teaching - learning course is up to date and reach the needs of learners, parents and communities, including get the internal strong support into the same direction. 2) External factors, Phuket Wittayalai Confucius Classroom is located on the stronghold, its geographic is on the natural environment surrounded are suitable for the learners to study Chinese. Besides that, many agencies from the public, the private, the association and the federation authority in Phuket also strongly support the Chinese teaching – learning. Lots of opportunities for students to show their full abilities on Chinese and Chinese culture and other special talents, these actions impact the good image of teaching – learning of the Confucius Classroom, Phuket Wittayalai School and are accepted widely. And 3) Others factors as Phuket Wittayalai Confucius Classroom was appointed to be responsible for the Center to Promote Chinese teaching – learning and Confucius Classroom respectively. Confucius Classroom, Phuket Wittayalai School also has various education resources, having cooperative program both within and outside the country as a partnership school resulting the completeness of Chinese teaching - learning at Phuket Wittayalai Confucius Classroom.